Optical Modulation Effects in Indium Oxide Films. (1977) - Avaritsiotis, J.; Howson, R. P.
Abstract : Tin doped indium oxide films produced by chemical vapour deposition and by d.c. sputtering have shown an optical reflectance spectra which can be modulated in the region of the plasma edge in the near infra-red by an electric field applied to the surface through an electrolyte. The effect produced could be quantitatively predicted by a theory developed for surfaces whose optical properties were controlled by their free carrier properties and for the sample being in thin film form. The plasma edge for films prepared by chemical vapour deposition on some occasions showed a modified plasma edge effect which was attributed to surface plasmons allowed by roughness effects.